2007
DOI: 10.1300/j010v45n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Profile of Elderly Patients Discharged from a Community Hospital

Abstract: Social workers have historically been an advocate for vulnerable groups. One such vulnerable group is elderly patients who have been shown to have multiple, chronic health problems. The current fiscal environment favors shortened lengths of stay, potentially leaving these vulnerable patients at risk for adverse outcomes upon discharge, especially Hospital (Ontario, Canada). The objectives were to (1) estimate the number of elderly people who indicate biopsychosocial risk for adverse outcomes, (2) determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…While it has been noted that without effective intervention, surgery patients may have substantial unmet psychosocial needs [29], from the current review, the outcomes reported from such interventions were mixed. One study found that "preoperative patient teaching" had no significant effect, and had minimal impact on the patient's ability to cope with anxiety [35].…”
Section: Psychosocial Interventionsmentioning
confidence: 78%
See 4 more Smart Citations
“…While it has been noted that without effective intervention, surgery patients may have substantial unmet psychosocial needs [29], from the current review, the outcomes reported from such interventions were mixed. One study found that "preoperative patient teaching" had no significant effect, and had minimal impact on the patient's ability to cope with anxiety [35].…”
Section: Psychosocial Interventionsmentioning
confidence: 78%
“…In summary and acknowledging the ranked quality and relevance of articles, four of the highly ranked articles emphasised the link between psychosocial issues, poorer treatment outcomes and longer hospital stays [5,14,27,29]. This underscored the importance of these connections.…”
Section: Psychosocial Factors and Surgerymentioning
confidence: 99%
See 3 more Smart Citations